Online Reading Resources Among EFL Students: Do They Promote Reading Habit? DO THEY PROMOTE READING HABIT? - Estika Satriani (J-SHMIC : Journal of English for Academic, 2019)
The aim of this study are to describe the EFL learners’ reading habit, the factors influence of reading habit, and the impact of the use Online Reading Resources on promoting students’ reading habit. 156 EFL learners FKIP- Islamic University of Riau involved as participants who read by using online reading resources. The study employed questionnaire, reading log, and interview intensively to collect the data. The results of analysis data from instruments were used in this study reflected that the use of online reading resources as a source of reading material has changed the reading habits of the learners, from conventional reading cultures into integrated the new technologies in reading process. There were 75% students already have got reading habit. It was significant increase than before. Besides that, online reading resources also provided positive changes for students who have low motivation in reading to be a fun reading activity. Supporting of teacher, parents, and environment help the learners establish their reading habit. The significant reason of learners get the reading habit was to complete the task. The result implies that the learners expected to read more and intensively to get the greatly reading habit. In conclusion, online reading resources are helpful to work the task, to get much information, and to improve learners’ knowledge in reading.